97 Primary malignant vaginal melanoma: single institution's experience of 52 cases. (18th September 2019) - Phoolcharoen, N; Frumovitz, M; Jazaeri, A; Chrisholm, GB; Onstad, M
Abstract : Objectives: To assess clinical and pathologic features that impact outcome in patients with vaginal melanoma. Methods: This is a retrospective review of vaginal melanoma cases treated at single institution between 1990 – 2015. Clinical and pathological characteristics were reviewed. Progression-free survival (PFS) and overall survival (OS) were calculated from the first treatment date. Results: Fifty-two patients with median age of 60.5 years (32.0–86.0) were identified. Using the AJCC clinical staging, 11.5% were stage I, 61.6% were stage II, 19.2% were stage III and 7.7% were stage IV. The median tumor size was 3.0 cm with median tumor thickness 8.0 mm. 81% experienced disease recurrence with 40.5% local recurrence, 23.8% distant recurrence and 35.7% both. Overall, the median PFS was 8.9 months with a 5-year PFS of 16%. The OS was 19.8 months with a 5-year OS of 18%. 44 patients underwent surgery as part of their primary therapy while 8 women did not have surgery. Patients who underwent surgery had a median OS 20.7 VS 9.3 months for those who did not (p<0.01). Patients who were diagnosed as stage I-II had significantly longer survival than patients who were stage III-IV (median OS 24.4 VS 13.4 months, p=0.03). In addition, patients who underwent pelvic exenteration had significantly longer survival (median OS 28.9 VS 17.2 months, p=0.02). Conclusions: Vaginal melanoma most commonly presents at an early stage but is still associated with poor outcomes. Patients who have localized disease, who are able to undergo primary surgical treatment and who undergo pelvic exenteration have longer OS.